The Impact of Immunoglobulin Replacement Therapy on Antibiotic Need in Adult Patients with Inborn Errors of Immunity - Esra Karabiber (Haseki Tıp Bülteni)
Aim: Patients with inborn errors of immunity (IEI) have a higher frequency of infections and long-term antibiotic usage. We aimed to assess the effects of immunoglobulin replacement therapy (IgRT) on infection rates, antibiotic usage, and treatment outcomes in patients with IEI. Methods: We retrospectively analyzed demographic data, infection frequency, antibiotic prescriptions, and IgRT in 122 IEI patients between March 2014 and September 2023. Specific IEI diagnoses were made following the European Society for Immunodeficiencies criteria. Results: The median age of patients was 29 years [interquartile range (IQR): 23-40], with 54.1% being male. The median age at diagnosis was 25 years (IQR: 13-36), with a diagnostic delay of 96 months (IQR: 24-180). IgRT was administered to 74.5% of patients, with a median treatment duration of 20 years (IQR: 10-33.5). Antibiotic use was higher in patients receiving IgRT (median: 27, IQR: 16-42) compared to those not on IgRT (median: 14, IQR: 8-22; p<0.001). Patients with bronchiectasis had lower baseline immunoglobulin G, CD19+, and natural killer cell counts, with more frequent antibiotic use, though hospitalization rates were similar to those without bronchiectasis. Immunoglobulin replacement therapy use was higher in the bronchiectasis group (61.5%, p<0.001). No significant differences in antibiotic use or hospitalization rates were observed between intravenous and subcutaneous IgRT groups. Conclusion: Patients with IEI face significant respiratory infections despite IgRT and prophylactic antibiotics. Bronchiectasis is a key risk factor for increased antibiotic use. Early diagnosis and personalized treatment are crucial in reducing infection burden and improving outcomes in this population.